Students’ Perceptions of Poster Oral Presentation in English - Hidayati, Diyah Nur (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This study investigated students’ perception on the use of poster oral presentations (POPs) in English to teach an English course. Employing a qualitative research approach, the investigation involves comprehensive examinations through interviews and an observation conducted with students to gauge the effects of this educational intervention on their language acquisition and communication capabilities. The findings suggest that the instructional design of Poster Oral Presentations (POPs) in English employs a structured learning procedure, including sessions on learning the concept of scientific poster presentations, research, content development, poster creation, English presentation delivery, and formal presentations. These findings also reveal that these activities are engaging and enjoyable for students, fostering active participation, vocabulary development, practical language application, and improved communication, teamwork, and critical thinking skills, though it highlights the need for more comprehensive understanding during discussions to address occasional challenges in language comprehension. The findings arising from this research have implications for educators, curriculum designers, and policymakers, offering insights into the practicality of utilizing POPs as an immersive and effective method for enhancing students' English language skills . Ultimately, this investigation contributes to the ongoing discourse surrounding innovative educational methodologies, yielding a deeper comprehension of how innovative pedagogy can profoundly influence language acquisition and communication proficiencies.